Landscape of the complete RNA chemical modifications in the human 80S ribosome. Issue 18 (7th September 2018) - Taoka, Masato; Nobe, Yuko; Yamaki, Yuka; Sato, Ko; Ishikawa, Hideaki; Izumikawa, Keiichi; Yamauchi, Yoshio; Hirota, Kouji; Nakayama, Hiroshi; Takahashi, Nobuhiro; Isobe, Toshiaki
Abstract: During ribosome biogenesis, ribosomal RNAs acquire various chemical modifications that ensure the fidelity of translation, and dysregulation of the modification processes can cause proteome changes as observed in cancer and inherited human disorders. Here, we report the complete chemical modifications of all RNAs of the human 80S ribosome as determined with quantitative mass spectrometry. We assigned 228 sites with 14 different post-transcriptional modifications, most of which are located in functional regions of the ribosome. All modifications detected are typical of eukaryotic ribosomal RNAs, and no human-specific modifications were observed, in contrast to a recently reported cryo-electron microscopy analysis. While human ribosomal RNAs appeared to have little polymorphism regarding the post-transcriptional modifications, we found that pseudouridylation at two specific sites in 28S ribosomal RNA are significantly reduced in ribosomes of patients with familial dyskeratosis congenita, a genetic disease caused by a point mutation in the pseudouridine synthase gene DKC1 . The landscape of the entire epitranscriptomic ribosomal RNA modifications provides a firm basis for understanding ribosome function and dysfunction associated with human disease.